2013
DOI: 10.2477/jccj.2012-0018
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Oxygen Composition and Carbon Impurity on Electronic Reliability of HfO2 Thin Films

Abstract: Highly reliable gate stack systems using a high-k dielectric thin film such as a hafnium dioxide film are indispensable for the development of ULSI (Ultra-Large-Scale Integration) devices. In this study, the degradation mechanisms of the electronic reliability of hafnium dioxide dielectric film caused by point defects such as oxygen vacancies and carbon interstitials was investigated by using quantum chemical molecular dynamics method. The magnitude of the band gap of the HfO 2-x , which is hafnium dioxide wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Thus, the difference in ε r value might be determined by the relative fractions of the tetragonal and orthorhombic phases or the defect concentration, which is expected to decrease the average dielectric constant with local lattice distortions. The ε r value of the tetragonal phase (35)(36)(37)(38)(39)(40) was higher than that of the orthorhombic phase (25)(26)(27)(28)(29)(30). Thus, the high ε r value of TEMA HZO capacitor indicates that it has a higher tetragonal phase fraction compared to the TDMA HZO capacitors.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Thus, the difference in ε r value might be determined by the relative fractions of the tetragonal and orthorhombic phases or the defect concentration, which is expected to decrease the average dielectric constant with local lattice distortions. The ε r value of the tetragonal phase (35)(36)(37)(38)(39)(40) was higher than that of the orthorhombic phase (25)(26)(27)(28)(29)(30). Thus, the high ε r value of TEMA HZO capacitor indicates that it has a higher tetragonal phase fraction compared to the TDMA HZO capacitors.…”
Section: Resultsmentioning
confidence: 88%
“…However, they reported that the increase in C concentration did not result in the decrease of the free energy difference between the orthorhombic and monoclinic phase [34]. In Kuenneth et al's work, the substitutional C defects were considered, although the C impurities are generally known as interstitial defects in HfO 2 [33,35]. Therefore, the theoretical calculations did not clearly reveal that the C impurities could decrease [12]), HZO is presented the free energy difference between the tetragonal and orthorhombic phases.…”
Section: Resultsmentioning
confidence: 99%
“…These defects can adversely affect the performance of devices. Also, they can create an electric field which can change band offsets and disrupt its dielectric properties [49].…”
Section: Hf-based High-κ Dielectricsmentioning
confidence: 99%
“…. Initial structures of (a) HfO2 with one oxygen vacancy and (b) HfO2 with one interstitial for quantum chemical molecular dynamics simulation [49].…”
Section: Hf-based High-κ Dielectricsmentioning
confidence: 99%